Can We Motivate Students to Practice Physical Activities and Sports Through Models-Based Practice? A Systematic Review and Meta-Analysis of Psychosocial Factors Related to Physical Education - Sierra-Díaz, Manuel Jacob; González-Víllora, Sixto; Pastor-Vicedo, Juan Carlos; López-Sánchez, Guillermo Felipe (Frontiers in Psychology, 2019)
Adults (more than 18 years old) are likely to reproduce the habits that they acquired during childhood and adolescence (from 6 to 16 years old). For that reason, teachers and parents have the responsibility to promote an active and healthy lifestyle in children and adolescents. Even though every school subject should promote healthy activities, Physical Education (PE) is the most important subject to foster well-being habits associated to healthy lifestyle during sport practice and other kinds of active tasks. Indeed, there are many factors that influence the acquisition of healthy habits that should be taken into account when programs and activities are implemented in both educational and extracurricular context. In this sense, psychological and social factors are of utmost importance to achieve optimal experiences for an active and healthy lifestyle. However, due to the myriad of studies analyzing different factors in different contexts, there could be confusion when programs and pedagogical strategies are applied in educational or extracurricular contexts. The objective of this investigation is to analyse the state of art of the psychosocial factors which influence the engagement in physical activities and sport practice. The keywords used in this review were mainly: “Self-Determination Theory,” “(intrinsic) motivation,” “Psychological need satisfaction,” “physical activity and sport engagement,” “Elementary Education,” “Secondary Education,” “Physical Education.” In addition, the Boolean data type “and,” “or,” and “not” were also used. The articles were selected according to the following criteria: (a) peer-reviewed original research published in international journals indexed in JCR or SJR, (b) published in English or Spanish, (c) about psychosocial factors which influence the physical activity and sport engagement, (d) in educational or extracurricular context. Research articles selected were found through Web of Science, Scopus, Google Scholar, SportDiscus (EBSCO-host), ERIC, PubMed, Medline, and PsycInfo databases. It was observed that physical activities and sport practice engagement are closely related to psychological factors. In particularly, intrinsic motivation was able to determine the active participation in any activity, including physical activity and sport practice during the implementation of Small-Sided Games and other kinds of pedagogical strategies (e.g., Pedagogical Models). Motivation was also closely related to flow state. Finally, these variables should be considered in order to organize effective programs to promote an active and healthy lifestyle in Physical Education classes.